Answer:
the third one
Step-by-step explanation:
bc like there are 2 boxes of 1 and 5 boxes of 1/6 so thats already 2 and 5/6 which applies to all of them. then there is 1 box of 1 and 2 boxes of 1/3 so thats 1 and 1/3 which applies to all of them also but when you make them have the same denominator you get 2 and 5/6 + 1 and 4/6 which deletes the second one. When you add you should get the same denominator so that deletes the first one so then you simplify that and the fraction should still be equal to the unsimplified fraction so you should get 4 and 1/2 if that makes sense
Answer:
3x = 2(-3x + 1)
Step-by-step explanation:
I think that's it I think it could be wrong but I tried
The tangent line to <em>y</em> = <em>f(x)</em> at a point (<em>a</em>, <em>f(a)</em> ) has slope d<em>y</em>/d<em>x</em> at <em>x</em> = <em>a</em>. So first compute the derivative:
<em>y</em> = <em>x</em>² - 9<em>x</em> → d<em>y</em>/d<em>x</em> = 2<em>x</em> - 9
When <em>x</em> = 4, the function takes on a value of
<em>y</em> = 4² - 9•4 = -20
and the derivative is
d<em>y</em>/d<em>x</em> (4) = 2•4 - 9 = -1
Then use the point-slope formula to get the equation of the tangent line:
<em>y</em> - (-20) = -1 (<em>x</em> - 4)
<em>y</em> + 20 = -<em>x</em> + 4
<em>y</em> = -<em>x</em> - 24
The normal line is perpendicular to the tangent, so its slope is -1/(-1) = 1. It passes through the same point, so its equation is
<em>y</em> - (-20) = 1 (<em>x</em> - 4)
<em>y</em> + 20 = <em>x</em> - 4
<em>y</em> = <em>x</em> - 24
Answer:
y = 0.5x
Step-by-step explanation:
The equation of a line in slope- intercept form is
y = mx + c ( m is the slope and c the y- intercept )
y = 0.5x - 2 ← is in slope- intercept form
with slope m = 0.5
Parallel lines have equal slopes, thus
y = 0.5x + c ← is the partial equation
To find c substitute (- 2, 1) into the partial equation
- 1 = - 1 + c ⇒ - 1 + 1 = 0
y = 0.5x + 0 , that is
y = 0.5x ← equation of parallel line
Answer:
62
Step-by-step explanation:
well, we start by expressing the number:
a b
we understand that using the above expression, the value of the number is 10a + b
using the information in the question,
a = 3b (1)
and,
11b + 11a = 88 (2) (derived using 10a + b form)
hence, when substituting (1) into (2):
11b + 33b = 88
44b = 88
b = 2 (3)
sub (3) into (1)
a = 6
hence, the number is 62